Burden of eclampsia: a persisting problem in the developing countries - Babbar, Kavita; Armo, Meena; Murthy, Madhumita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Hypertensive disorders of pregnancy constitute one of the major threats to maternal health. Eclampsia is still a leading cause of maternal morbidity and mortality in developing countries. This study was carried out to determine the incidence of eclampsia, demographic profile of patients, obstetric outcome, fetal outcome, maternal morbidity and mortality. Methods: A 5 year retrospective observational study included 521 patients who presented in emergency with eclampsia and admitted between April 2010 and March 2015, in the department of Obstetrics and gynecology, government medical college (Chhattisgarh institute of medical sciences) and tertiary care hospital Bilaspur, Chhattisgarh. Results: Based on 14,876 pregnancies in the 5 year period in our referral hospital, we estimated an incidence of 3.5%.70.8% were primigravida and 86.4% of patients had no regular antenatal care. Majority of the cases (82.1%) presented as antepartum/intrapartum eclampsia in the age group 20-24 years (65.4%).The patients usually presented at term(62.4%) with 69.7% having vaginal delivery as compared to 30.3% undergoing LSCS. The fetal outcome showed 56.2% live-births, 25.5% had early neonatal death and 13.3% still-born. The complications most commonly observed were puerperal sepsis ( 11 %),oliguria(8.1%), pulmonary edema(5.9%) and maternal mortality as 8.4 %. Conclusions: Most of the life-threatening eclampsia cases can be prevented by simple awareness and motivation towards antenatal care. In Chhattisgarh state where majority of rural population are tribal, illiterate, living in difficult to reach areas, delay in referral, due to unavailability of clinicians or medical officers in peripheral areas for antenatal examination.The best way to reduce the burden is by creating an awareness, proper antenatal care, timely referral and thus prevent the occurrence of eclampsia.